Mechanical Performances of Twill Kenaf Woven Fiber Reinforced Polyester Composites - Ismail, Al Emran; Khalid, Siti Nor Azila; Zainulabidin, Muhd Hafeez; Tajul Arifin, Ahmad Mubarak; Hassasn, Mohd Fahrul; Ibrahim, Mohd Rasidi; Rahim, Muhammad Zulafif (International Journal of Integrated Engineering, 2018)
Natural fibres have been explored by many researchers. Natural fibres have the potential aspect to replace glass fibre in fibre-reinforced composites application. Kenaf is also one of the selected natural fibres that have bio resource profit regarding on their capability to absorb energy absorption especially. This study focused on the twill yarn kenaf woven composite structure. Composites were prepared using the hand lay-up method with different type of orientation each layered arrangement by Taguchi. The hardened composites were cured for 24 hours before it was shaped according to ASTM D3039. Taguchi method is used in this study for optimization which can reduce the time consumed rather than using experimental approach. The result shows orientations were significant on tensile and modulus strength performances. After optimizations, the values of tensile and modulus strength was 55.738 MPa and 5761.704 Joule, which is increasing 3.77% for tensile strength and 4.23% for Young modulus. By comparing fracture mechanism before and after optimizations, there was clear decreasing fracture surface. It indicated that, the mechanical behavior performances of the twill woven kenaf reinforced composites can be effectively improved by this method.